Perempuan dan Narasi Kekerasan: Studi Kritis Peran Gender dalam Deradikalisasi - Abdul Ghofur; Sulistiyono Susilo (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2015)
Radicalism is a process initiated from the ideas and teachings that stem from individual stages. Hence, the early detection effort in deradicalization by involving women can run effectively, regarding the fact that women play a vital role in the family, particularly in shaping the character of children. Unfortunately, women's role in preventing or promoting and participating, terrorism, and political violence seem to be neglected. This qualitative study attempts to examine the role of women in preventing radicalization and at the same time promoting and participating in alleviating terrorism and political violence. The findings of the study reveal that the role of women in the deradicalization can be done in a number of strategies, although not restricted, such as reduction of gender inequality and disparity, giving women a greater role to participate in a multi-field of the social realm, strengthening the well-being to prevent radicalization, making women as leaders who hold moderate and tolerant values in education, especially within, though not limited, the family environment, and initiating peace through women’s reproductive functions.